PEMBERDAYAAN KESEHATAN MELALUI PENYULUHAN YANG BERTEMA PENYAKIT TUBERCULOSIS PADA ANAK USIA DINI - Denai Wahyuni; Henny Maria Ulfa; Firman Edigan; Yeyen Gumayesty (LPPM UMRI, 2019)
Age of child is a very prone age to the transmission of the disease tubercolosis. The rate of transmission and danger of high transmission is in the age of 0-6 years and the age of 7-14 years. The age of children is very prone to contracting tubercolosis when infected they are easily affected by the disease tubercolosis. Consciousness, the participation of students is needed prevention efforts, eradication of Tubercolosis disease. There are still many early childhood children understanding of the disease Tubercolosis, the devotion of the knowledge of early childhood to better understand, applying that the importance of prevention of the disease tubercolosis. To the mother and father of teachers, to provide supervision and education to students in the school Keywords: Tuberculosis, disease, interception